Exploring Actinomycetes metabolites in cancer therapy - R., Jayanthi; K., Muthukumar; Durai, Latha (International Journal of Research in Medical Sciences, 2025)
Cancer poses a serious threat to human health, with its incidence and mortality rates rapidly increasing worldwide. Current therapies often fall short of clinical needs, particularly due to challenges such as tumor resistance to chemotherapy and severe toxic side effects. Therefore, there is an urgent need to develop highly effective anticancer drugs with low toxicity. Natural products derived from microorganisms serve as a vital source of valuable pharmaceuticals and therapeutic agents. Among them, actinomycetes represent a rich reservoir for the discovery of numerous medicinal natural products and play a crucial role in the development of new microbial drugs. In particular, actinomycetes of the genus Streptomyces have attracted significant global attention due to their ability to produce a wide range of bioactive secondary metabolites. The potential of these Gram-positive bacteria to synthesize diverse compounds with potent biological activities makes them ideal candidates for anticancer drug discovery. This review article focuses on the natural products secreted by actinomycetes, their biological functions and their possible roles in anticancer activity.